(untitled) (MAUSAM, 2026)
During the past three years, new insights have been gained into the convective features and microphysical characteristics of heavy rainfall in South China, which is a typical monsoon coastal area. Such improved understanding is closely related to the rapid progress of application of advanced remote sensing techniques, in particular the upgrade of the dual-polarization function of the operational weather radars in South China. This paper reviews the representative studies since approximately 2019 in three aspects. First, spatiotemporal distribution and diurnal propagation of the convection initiation during the warm season. Second, general features and synoptic-scale environments of the meso-beta-scale convective systems (MCSs) during the pre-summer rainy season (April to June). Third, microphysical characteristics of the extreme short-term rainfall and the coexisting frontal and warm-sector heavy rainfall in South China.